Strategi Pemasaran Melalui Kompetensi Kewirausahaan dalam Mencapai Peningkatan Kinerja UMKM - Raysa Alevia Permana; R. Deni Muhammad Danial; Resa Nurmala (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Beverage MSMEs in Sukabumi City have experienced a decline in sales growth. In addition to the impact of Covid-19 several years ago, this is also caused by the fact that MSME players do not understand the performance of MSMEs, marketing strategies and entrepreneurial competencies to improve MSME performance. This study aims to determine the effect of marketing strategies and entrepreneurial competencies in achieving improved MSME performance and to determine how entrepreneurial competencies mediate marketing strategies on MSME performance. The methods used in this research are descriptive and associative methods through a quantitative approach. The population in this study were beverage MSME players in Sukabumi City who used and were interested in the performance of MSMEs. The sample used in this study amounted to 210 beverage MSMEs in Sukabumi City. The sample was taken based on Hair J theory, that the determination of the sample size was 5 times the number of research instruments. The research data used in this study include primary data and secondary data, namely observation, interviews, questionnaires, literature studies, and documentation. The results of this study are There is a significant influence between marketing strategy variables and entrepreneurial competence on MSME Performance and Entrepreneurial Competence can mediate the relationship between marketing strategies and MSME Performance in beverage business actors in Sukabumi City.